Preparation and performance of new antifouling resins containing BIT group. Issue 2 (17th January 2019) - Fu, Ying; Du, Hui; Chen, Zhaojun; Liu, Xin; Zhang, Xiaodong
Abstract: New acrylate grafting epoxy antifouling resins containing benzoisothiazoline ketone (BIT) group were successfully synthesized, and their structures and performances were determined. Experimental data indicated that the new acrylate grafting epoxy antifouling resins have a strong bonding to the cured epoxy resin coating through chemical reaction and self-stratifying. And the paint prepared by using the new resin as matrix has excellent self-polishing and antifouling properties. Especially its antifouling period could be modified by changing the weight ratio of the usage of the mixed monomers and epoxy resin in the preparing process of the acrylate grafting epoxy antifouling resins.